In-Vitro Analysis On The Effects Of UV-B Radiation On The Dorsal Skin Melanophores Of Indian Bullfrog Hoplobatrachus Tigerinus - SHARIQUE A.ALI,; SAIMA SALIM,; AYESHA S. ALI,; JAYA PETER, (International Journal of Pharma and Bio Sciences, 2011)
In vitro studies on the dorsal integumental melanophores of amphibian Hoplobatrachus tigerinus revealed that the artificial UV-B radiation (313nm) at a dose range from 20.0 - 24.6 µW/cm 2 for a continuous period of 60- 120 minutes caused an irreversible damage and disruption to the melanophores resulting into permanent clumping and aggregation of cells. However, at lower duration of exposure, the melanophores showed gradual pigment dispersion, most likely as an innate mechanism of defense to attenuate the UVB causing damage.